TEMPERATURE EXHAUST GAS ANALYSIS ON THE SHIP ENGINE - Dwi Prasetyo (Jurnal Rekayasa Mesin, 2022)
Dual-fuel diesel engine is an engine with the use of two fuels in the combustion process to get labor on the engine. The types of fuels used include methane gas and marine gas oil fuels. Methane is produced from vapor cargo tank liquified natural gas. The purpose of this study was to determine what causes high exhaust gas temperatures on the performance of the dual-fuel diesel engine using the fault tree analysis data analysis method. From the analysis of the research data, several problems were formulated, namely, the factors that could cause high exhaust gas temperatures in the dual fuel diesel engine were the lack of combustion air supply in the engine combustion chamber, incompatible combustion composition between oil and gas fuel, and the engine room that is extremely hot. The impact caused is damage to the machining components and decreased performance of the dual-fuel diesel engine. To overcome the decrease in work on the dual fuel diesel engine is to carry out maintenance and repair on every component of the engine that has problems and damage in accordance with standard procedures.